Turkmenistan : An Assessment of Leasehold-based Farm Restructuring - Lerman, Zvi (Washington, DC: World Bank, 2013)
Turkmenistan's unique approach to land reform and farm restructuring has produced a significant shift to individual or household-based farming, with more than three-quarters of the arable land leased to individual households or small groups. Most leaseholders consider this land to be rightfully theirs, and they expect to keep it in the future, either as private owners, or through extension of their leasehold. However, individual production is administratively circumscribed by a pervasive system of state orders and central planning. The lease contracts rigidly specify the crop that each leaseholder is required to produce (typically cotton or wheat) and set a specific quantity target for delivery to the state at prices much below the level of prices on international markets. Managers and leaseholders universally express the view that the prices they receive from the state for wheat and cotton are too low, and identify the chance to sell freely at open market proces as a key factor that would improve the economic situation on farms. Both managers and leaseholders expressed enthusiasm for the reform at the time of the survey. This is a natural psychological reaction to the dramatic transition to a new system, and to avoid disillusionment, the initial change must be followed by further meaningful reforms, including abolition of state orders, transfer of land to individual control, and elimination of constraints on individual choice.